FIGURE 6. Paralomis birsteini Macpherson, 1988 in Lithodidae from the Ross Sea, Antarctica, with descriptions of two new species (Crustacea: Decapoda: Anomura) - Ahyong, Shane T.; Dawson, Elliot W. (Zenodo, 2006)
FIGURE 6. Paralomis birsteini Macpherson, 1988, male (cl 79.4 mm, cw 76.4 mm, NIWA 24217). A, carapace, dorsal view. B, abdomen. C, right chela, outer surface. D, left chela, outer surface. Published as part of Ahyong, Shane T. & Dawson, Elliot W., 2006, Lithodidae from the Ross Sea, Antarctica, with descriptions of two new species (Crustacea: Decapoda: Anomura), pp. 45-68 in Zootaxa 1303 on page 57, DOI: 10.5281/zenodo.173679